Recent advances in understanding the effects of climate change on the world's oceans. (4th August 2019) - Hollowed, Anne B; Barange, Manuel; Garçon, Véronique; Ito, Shin-ichi; Link, Jason S; Aricò, Salvatore; Batchelder, Harold; Brown, Robin; Griffis, Roger; Wawrzynski, Wojciech
Abstract: In June 2018, >600 scientists from over 50 countries attended the Fourth International Symposium on the Effects of Climate Change on the World's Oceans (ECCWO-4). ECCWO-4 provided a forum for scientists to share information, build understanding, and advance responses to climate impacts on oceans and the many people, businesses and communities that depend on them. Seven Key Messages emerging from the symposium and relevant information from recently published literature are summarized. Recent scientific advances are improving our ability to understand, project, and assess the consequences of different levels of 21st century climate change for ocean ecosystems and ocean dependent communities. Outcomes of the symposium highlighted the need for on-going engagement with stakeholders, communities, and managers when considering the trade-offs associated with tactical and strategic opportunities for adaptation to climate change. Science informed adaptation frameworks that engage the public in their development are needed for effective management of marine resources in a changing climate. The summary provides a brief overview of the advances in climate-ocean science emerging from the symposium and provides context for the contributed papers within the broader socio-ecological advances of the discipline.